Mutya ng Pasig - Padilla, Jose; Gonzales, Rebecca; Belarmino, Teody; Nite, Roger; Delia, Razon (LVN Pictures, 2004)
A supernatural melodrama of a woman's misfortune and suffering interwoven with the legend of the Pasig. Mercedes, aside from being the town's current mutya (fiesta queen), is about to be married to her childhood sweetheart. Unknown to them, Dr. Modesto Millar is also secretly in love with Mercedes. One night, Modesto's house is robbed and the blame is placed on Mercedes' groom-to-be. He is arrested and imprisoned after which Modesto courts Mercedes and eventually marries her. When the former fiance is finally released, gossip spreads about him and Mercedes. Consumed by anger and jealousy and believing the superstitious talk that the baby girl is not his because of an ugly birthmark, he banishes Mercedes and the child, chased by his monstrous dog, and she drowns in the river. From that point on, a legend spreads about a woman, a sirena (mermaid), haunting the river singing a sad but beautiful song. Mercedes' daughter is saved by a childless couple, Tolindoy and Angge, and grows into a lovely woman inheriting her mother's love for music. She is betrothed to Basilio, the son of Mercedes' former flame. When Delia becomes the town's mutya, a commotion ensues and in the dead of night, she takes a banca and ventures into the dark river. Basilio is frantic and searches for her, believing she may have drowned. He hears the haunting song and witnesses the apparition, but it is no sirena, but the ghost of the lovely Mercedes, hovering over a bed of water lilies with the practically lifeless body of her daughter at her feet. Mercedes is singing the haunting kundiman "Ako ang Mutya ng Pasig". The townspeople take the unconscious Delia to Don Modesto but at first he refuses to treat the young woman until he sees the birthmark on the young woman's shoulder. He finally realizes the truth and finally accepts Delia as his daughter.